Variability of Biological Indications of Winter Wheat Varieties in Saline Soil Conditions - Kushiev Kh. Kh; Saidzoda M; Khujamberdiev Ch. T; Kuliev T. Kh (American Journal of Biology and Natural Sciences, 2024)
The article clarifies results of conducted researches of specific variation and determinacy of winter wheat of Triticum aeustium type indications in salinated soil conditions. There was noted peculiarities of wheat ear mass and wheat ear quantity strong determinacy while onthogenetic development of winter wheat. Also there were identified weak, average and strong correlation bonds’ levels between biologic indications of wheat.